Selective expansion of donor‐derived regulatory T cells after allogeneic bone marrow transplantation in a patient with IPEX syndrome. (7th November 2013) - Horino, Satoshi; Sasahara, Yoji; Sato, Miki; Niizuma, Hidetaka; Kumaki, Satoru; Abukawa, Daiki; Sato, Atsushi; Imaizumi, Masue; Kanegane, Hirokazu; Kamachi, Yoshiro; Sasaki, Shinya; Terui, Kiminori; et al.
Abstract IPEX syndrome is a rare and fatal disorder caused by absence of regulatory T cells (Tregs) due to congenital mutations in the Forkhead box protein 3 gene. Here, we report a patient with IPEX syndrome treated with RIC followed by allogeneic BMT from an HLA‐matched sibling donor. We could achieve engraftment and regimen‐related toxicity was well tolerated. Although the patient was in mixed chimera and the ratio of donor cells in whole peripheral blood remained relatively low, selective and sustained expansion of Tregs determined as CD4+CD25+Foxp3+ cells was observed. Improvement in clinical symptoms was correlated with expansion of donor‐derived Tregs and disappearance of anti‐villin autoantibody, which was involved in the pathogenesis of gastrointestinal symptoms in IPEX syndrome. This clinical observation suggests that donor‐derived Tregs have selective growth advantage in patients with IPEX syndrome even in mixed chimera after allogeneic BMT and contribute to the control of clinical symptoms caused by the defect of Tregs.